الهيئة المكلّفة بالرّقابة على دستوريّة القوانين في الدّول المغاربية. - الشيخة, هوام (Université de M'sila, 2020)
الملخص: تشكّل الرّقابة على دستورية القوانين أهمّ دعائم دولة القانون، لأنّ الهدف منها هو الحفاظ على أسمى قاعدة قانونيّة في الدّولة هي الدّستور. و لتنتج هذه الرّقابة ثمارها و تشكّل حصنا منيعا يقف في وجه أيّ خرق لقواعد الدّستور من قبل السّلطتين التّشريعية و التّنفيذية لابدّ من وجود هيئة لها من التّركيبة البشريّة و الصّلاحيات القانونية ما يسهّل لها أداء مهامّها. و هو ما حاول المؤسّس الدّستوري في الجزائر، المغرب و تونس تجسيده في الهيئة المكلّفة بالرّقابة على دستورية القوانين. abstract : Censorship of the constitutionality of laws is the most important pillar of the rule of law, because its purpose is to preserve the highest legal rule in the state, the Constitution. In order for this censorship to bear fruit and constitute an impregnable bulwark against any violation of the Constitution by the legislature and the executive, there must be a body of human composition and legal powers to facilitate the performance of its tasks. This is what the constitutional founder in Algeria, Morocco and Tunisia tried to embody in the body charged with overseeing the constitutionality of laws.
Keywords: رقابة ; على ; سياسية ; قضائية ; Constitutional ; political ; judicial ; control